Bagattelle per una pandemia (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. La democrazia in pericolo? - 3. La libertà religiosa tra Costituzione e Concordato - 4. Sulla libertas Ecclesiae e sulle regole del diritto internazionale - 5. Le trattative diplomatiche de facto tra la CEI e il Governo e il dibattito pubblico - 6. Il FEC e il (mancato) trasferimento della proprietà delle chiese con personalità giuridica in favore dell’autorità ecclesiastica: un case study.Trifles for a pandemicABSTRACT: The emergency regulations for the containment of Covid-19 as well as affecting religious freedom (art. 19 of the Italian Constitution) can also be relevant from the point of view of the bilaterality of the pact between the Italian State and the Holy See by opening up to the principles of international law and the Vienna Convention the entrance to the list of instruments that can be applied for the solution of the problem, alongside the usual pragmatic instruments of realpolitik.